2016
DOI: 10.3389/fpsyt.2016.00024
|View full text |Cite
|
Sign up to set email alerts
|

Memory Systems and the Addicted Brain

Abstract: The view that anatomically distinct memory systems differentially contribute to the development of drug addiction and relapse has received extensive support. The present brief review revisits this hypothesis as it was originally proposed 20 years ago (1) and highlights several recent developments. Extensive research employing a variety of animal learning paradigms indicates that dissociable neural systems mediate distinct types of learning and memory. Each memory system potentially contributes unique component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 154 publications
(133 reference statements)
3
96
0
3
Order By: Relevance
“…Finally, numerous investigators have suggested that enhancement of the dorsal striatum-dependent memory system might in part underlie the development of some neuropsychiatric disorders, in particular disorders with prominent habit-like behavioral features (White, 1996, Everitt and Robbins, 2005, Schwabe et al., 2011a, Berner and Marsh, 2014, Gillan and Robbins, 2014, Goodman et al., 2014, Goodman and Packard, 2016a, Goodman and Packard, 2016b). For instance, post-traumatic stress disorder (PTSD) is partly characterized by intractable avoidance behaviors that occur in response to trauma-related cues, and some investigators suggest that such avoidance symptoms may be a manifestation of enhanced DLS-dependent habit memory following very high levels of emotional arousal (i.e., trauma; Packard, 2009, Schwabe et al., 2010c, Goodman et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, numerous investigators have suggested that enhancement of the dorsal striatum-dependent memory system might in part underlie the development of some neuropsychiatric disorders, in particular disorders with prominent habit-like behavioral features (White, 1996, Everitt and Robbins, 2005, Schwabe et al., 2011a, Berner and Marsh, 2014, Gillan and Robbins, 2014, Goodman et al., 2014, Goodman and Packard, 2016a, Goodman and Packard, 2016b). For instance, post-traumatic stress disorder (PTSD) is partly characterized by intractable avoidance behaviors that occur in response to trauma-related cues, and some investigators suggest that such avoidance symptoms may be a manifestation of enhanced DLS-dependent habit memory following very high levels of emotional arousal (i.e., trauma; Packard, 2009, Schwabe et al., 2010c, Goodman et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…An increased desire to try new things, a need to ramp up one’s emotional state, and/or heightened worry over fitting in socially may tip adolescents into long-term maladaptive patterns. As an example, substance experimentation for some adolescents may alter neural circuitry underlying affective and cognitive processing and create reinforcing habits over time that lead to long term substance use disorders (Goodman and Packard, 2016). These mechanisms may be further enhanced by stressful experiences that are commonly encountered in adolescence (Goodman and Packard, 2016; Romeo, 2010; Spear, 2009).…”
Section: Heightened Emotionality In Adolescence: Form and Functionmentioning
confidence: 99%
“…This behavioral plasticity, often times maladaptive, must be associated changes in neural plasticity. In fact, it has been noted multiple times that there is a high degree of overlap between the neurobiology of learning and memory and the neurobiology of addiction (e.g., White 1996;Kelley 2004;Hyman et al 2006;Volkow et al 2014;Goodman and Packard 2016). Drugs of abuse are often linked to disrupted learning, but the relationship between drugs of abuse and learning is more complex as drug use and abuse is also associated with the development of strong but maladaptive memories that contribute to drug-seeking behavior and addiction.…”
mentioning
confidence: 99%